2020
DOI: 10.3389/fchem.2020.00628
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Mediated Annulation Approaches for Synthesis of Arylnaphthalene Lignan Lactones

Abstract: Arylnaphthalene lignan lactones belong to a class of natural lignans, and more than 60 analogs have been isolated. Their pharmacological activities as well as unique structural features have attracted considerable attention from medicinal and synthetic chemists. Since the first synthesis in 1895, many synthetic methodologies with ionic or pericyclic reaction mechanisms have been reported. Transition metal catalysts sometimes provide exceptional synthetic versatility for the syntheses of natural compounds. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The regioselectivity of the natural product synthesis is influenced by metal catalyst reaction [41]. Aryl naphthalene lignans are the end product of this metal-catalyzed process the entire synthesis of natural products [42]. In this process, an aryne and diyne were co-cyclized with palladium to target the naphthyl segments of Taiwanins C (30) and E(31) [43] as well as dehydrodesoxypodophyllotoxin (32).…”
Section: A Nucleophilic Addition To Benzynesmentioning
confidence: 99%
“…The regioselectivity of the natural product synthesis is influenced by metal catalyst reaction [41]. Aryl naphthalene lignans are the end product of this metal-catalyzed process the entire synthesis of natural products [42]. In this process, an aryne and diyne were co-cyclized with palladium to target the naphthyl segments of Taiwanins C (30) and E(31) [43] as well as dehydrodesoxypodophyllotoxin (32).…”
Section: A Nucleophilic Addition To Benzynesmentioning
confidence: 99%
“…Because of their important pharmacological properties, NALLs have attracted attention from the organic synthetic community since the pioneering synthetic work on these lignans in 1895 by Michael et al (1895) . Synthetic efforts have resulted in many impressive approaches toward these highly substituted 1-arylnaphthalenes and culminated in the total synthesis of a series of arylnaphthalene lactone-type lignans ( Chen et al, 2018 ; Zhao et al, 2018 ; Park et al, 2020 ). Methodologies for the construction of 1-arylnaphthalenes could be roughly classified into five categories: Diels–Alder type cycloaddition ( Brown et al, 1964 ; Holmes et al, 1971 ; Klemm et al, 1971 ; Takano et al, 1985 ; Stevenson et al, 1989 ; Padwa et al, 1996 ; Xiong et al, 2012 ; Kudoh et al, 2013 ; Kocsis et al, 2014 ; Park et al, 2014 ; Meng et al, 2016 ), benzannulation ( Ogiku et al, 1995 ; Flanagan et al, 2002 ; Nishii et al, 2005 ; Ishikawa et al, 2021 ; Moriguchi et al, 2021 ), Garratt–Braverman-type cyclization ( Mondal et al, 2011 ; Mondal et al, 2012 ), transition metal-mediated cyclization ( Murakami et al, 1998 ; Mizufune et al, 2001 ; Sato et al, 2004 ; Sato et al, 2007 ; Gudla et al, 2011 ; Patel et al, 2013 ; Wong et al, 2014 ; Kao et al, 2015 ; Naresh et al, 2015 ; Xiao et al, 2018 ), and other type of annulations ( Ogiku et al, 1990 ; Kamal et al, 1994 ; Ogiku et al, 1995 ; Harrowven et al, 2001 ; Foley et al, 2010 ; He et al, 2014 ; Hayat et al, 2015 ; Yamamoto et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other valuable synthetic methodologies utilizing key reactions such as the Blaise reaction-intramolecular [4 ? 2] reaction (He et al 2012), Garratt-Braverman cyclization Stevenson, 1971, 1973;Arnold et al 1973;Yamamoto et al 2015), benzoin condensation-thermal cyclization (Hayat et al 2015a, b), and transitionmetal catalyzed synthesis (Park et al 2020) have been reported.…”
Section: Introductionmentioning
confidence: 99%